2014
DOI: 10.1002/lary.24367
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for musculoskeletal problems associated with microlaryngeal surgery: A national survey

Abstract: Musculoskeletal symptoms are common (83%) among surgeons performing microlaryngeal surgery. Findings suggest multiple factors may contribute to development of MSSx in otolaryngologists. Risk factors for MSSx and taking breaks during surgery include average case operating time >30 minutes and absence of back support. Previous studies have identified neck flexion and lack of arm support as associated with risk of musculoskeletal injury. This study demonstrates that MSSx related to surgery do occur in otolaryngol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 16 publications
(31 reference statements)
7
46
0
Order By: Relevance
“…First, this study had a small sample size and was from a single institution, which may limit its generalizability. However, we had an excellent response rate of 68.6%, which compares very favorably to the literature . Additionally, assessment of the REBA score can be subjective, as most postural positions are scored based on both an angular and a time factor.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…First, this study had a small sample size and was from a single institution, which may limit its generalizability. However, we had an excellent response rate of 68.6%, which compares very favorably to the literature . Additionally, assessment of the REBA score can be subjective, as most postural positions are scored based on both an angular and a time factor.…”
Section: Discussionsupporting
confidence: 68%
“…However, we had an excellent response rate of 68.6%, which compares very favorably to the literature. 1,[8][9][10]19,20,[22][23][24] Additionally, assessment of the REBA score can be subjective, as most postural positions are scored based on both an angular and a time factor. A static picture can be used to accurately measure an angle, but does not capture the length of time a position is maintained or how many repetitions per minute occurred.…”
Section: Discussionmentioning
confidence: 99%
“…With longer or more difficult procedures, fatigue is an additional problem, particularly of the larger muscle groups (upper arm and shoulder). Musculoskeletal symptoms occur in around 83% of surgeons performing microlaryngeal surgery, previous studies have identified neck flexion, and lack of arm supports is associated with high risk of musculoskeletal injury…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal symptoms associated with performing microsuspension laryngeal surgery (MLS) are common. Wong et al found that 83% of otolaryngology survey respondents reported the presence of musculoskeletal symptoms while performing MLS, with some symptoms even persisting 48 hours after performing surgery . Accommodations to avoid pain associated with MLS need evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…RULA is a validated survey method developed to assess ergonomic postures in the occupational setting and estimate risk of injury . Despite this compelling data, 38% of otolaryngologists continue to report not using arm support during MLS . This highlights the lack of insight regarding the ergonomics of performing MLS.…”
Section: Introductionmentioning
confidence: 99%